International Accounting and Reporting Issues - 2016 Review - Conference des Nations Unies sur le commerce et le développement (United Nations, 2017)
The International Accounting and Reporting Issues Review presents country case studies on the interrelated topics of compliance monitoring and enforcement mechanisms in relation to corporate reporting, auditing and regulation of professional accountants within the context of achieving high-quality corporate reporting. These case studies are continuations of similar studies that have already been published previously.